In vitro induction of Entamoeba histolytica cyst-like structures from trophozoites. - Hugo Aguilar-Díaz; Martha Díaz-Gallardo; Juan P Laclette; Julio C Carrero (Public Library of Science (PLoS), 2010)
Inhibition of encystment can be conceived as a potentially useful mechanism to block the transmission of Entamoeba histolytica under natural conditions. Unfortunately, amoeba encystment has not been achieved in vitro and drugs inhibiting the formation of cysts are not available. Luminal conditions inducing encystment in vivo are also unknown, but cellular stress such as exposure to reactive oxygen species from immune cells or intestinal microbiota could be involved. A role for certain divalent cations as cofactors of enzymes involved in excystment has also been described. In this study, we show that trophozoite cultures, treated with hydrogen peroxide in the presence of trace amounts of several cations, transform into small-sized spherical and refringent structures that exhibit resistance to different detergents. Ultrastructural analysis under scanning and transmission electron microscopy revealed multinucleated structures (some with four nuclei) with smooth, thick membranes and multiple vacuoles. Staining with calcofluor white, as well as an ELISA binding assay using wheat germ agglutinin, demonstrated the presence of polymers of N-acetylglucosamine (chitin), which is the primary component of the natural cyst walls. Over-expression of glucosamine 6-phosphate isomerase, likely to be the rate-limiting enzyme in the chitin synthesis pathway, was also confirmed by RT-PCR. These results suggest that E. histolytica trophozoites activated encystment pathways when exposed to our treatment.